2020
DOI: 10.1186/s12985-020-01457-0
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the efficacy of HIV protease inhibitors against SARS-CoV-2′s main protease

Abstract: Background The pandemic caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has resulted in millions of infections worldwide. While the search for an effective antiviral is still ongoing, experimental therapies based on repurposing of available antivirals is being attempted, of which HIV protease inhibitors (PIs) have gained considerable interest. Inhibition profiling of the PIs directly against the viral protease has never been attempted in vitro, and while few studies reported an efficacy … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
61
1
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(70 citation statements)
references
References 33 publications
2
61
1
2
Order By: Relevance
“…Furthermore, from a computational point of view, docking studies have shown that ritonavir possesses a low affinity score (−6.4 kcal/mol) in comparison to other HIV protease inhibitors docked on M pro . While the IC 50 value of lopinavir proved to be rather unfavorable, ritonavir was the most effective among the panel of tested compounds by Mahdi M. and co-workers, with IC 50 of 13.7 µM [ 53 , 54 ]. Therefore, lopinavir was progressively replaced with other commercially available antiviral drugs in the protease inhibitor combinations.…”
Section: Sars-cov-2 M Pro Inhibitorsmentioning
confidence: 99%
“…Furthermore, from a computational point of view, docking studies have shown that ritonavir possesses a low affinity score (−6.4 kcal/mol) in comparison to other HIV protease inhibitors docked on M pro . While the IC 50 value of lopinavir proved to be rather unfavorable, ritonavir was the most effective among the panel of tested compounds by Mahdi M. and co-workers, with IC 50 of 13.7 µM [ 53 , 54 ]. Therefore, lopinavir was progressively replaced with other commercially available antiviral drugs in the protease inhibitor combinations.…”
Section: Sars-cov-2 M Pro Inhibitorsmentioning
confidence: 99%
“…Following viral RNA replication comes the translation and proteolytic processing of viral proteins. Here, HIV protease inhibitors such as atazanavir, saquinavir and ritonavir were considered as repurposing candidates against SARS-CoV-2's 3C-like protease alongside danoprevir, a hepatitis C protease inhibitor ( Chen et al, 2020 ; Mahdi et al, 2020 ). Disulfiram and famotidine were also proposed as repurposing candidates against SARS-CoV-2's papain-like protease ( Lin et al, 2018 ; Samimagham et al, 2020 ).…”
Section: Drug Repurposing Candidates For Covid-19mentioning
confidence: 99%
“…Saquinavir [DB01232] inhibiting HIV1/2 protease-mediated lysis of HIV gag and pol polyproteins was found cytotoxically active at conc. Above 50 μM [56]. Rupintrivir (DB05102) a broad-spectrum antiviral agent is a potent 3C-Like protease inhibitor against norovirus, picornavirus, and coronavirus proteases in development against human rhinoviral (HRV) infections that has been recently co-crystallized with its target [57].…”
Section: Protease Inhibitorsmentioning
confidence: 99%